Role of adrenergic receptors in shock - Geevarghese, Mathew; Patel, Krishna; Gulati, Anil; Ranjan, Amaresh K. (Frontiers in Physiology, 2023)
Shock is a severe, life-threatening medical condition with a high mortality rate worldwide. All four major categories of shock (along with their various subtypes) – hypovolemic, distributive, cardiogenic, and obstructive, involve a dramatic mismatch between oxygen supply and demand, and share standard features of decreased cardiac output, reduced blood pressure, and overall hypoperfusion. Immediate and appropriate intervention is required regardless of shock type, as a delay can result in cellular dysfunction, irreversible multiple organ failure, and death. Studies have shown that dysfunction and downregulation of adrenergic receptors (ARs) are often implicated in these shock conditions; for example, their density is shown to be decreased in hypovolemic and cardiogenic shock, while their reduced signaling in the brain and vasculature decrease blood perfusion and oxygen supply. There are two main categories of ARs, α, and β, each with its subtypes and distributions. Our group has demonstrated that a dose of 0.02 mg/kg body wt of centhaquine (CQ) specifically activates α2B ARs on venous circulation along with the central α2A ARs after hypovolemic/hemorrhagic shock. Activating these receptors by CQ increases cardiac output (CO) and reduces systemic vascular resistance (SVR), with a net increase in blood pressure and tissue perfusion. The clinical trials of CQ conducted by Pharmazz Inc. in India have demonstrated significantly improved survival in shock patients. CQ improved blood pressure and shock index, indicating better blood circulation, and reduced lactate levels in the blood compared to in-use standard resuscitative agents. After successful clinical trials, CQ is being marketed as a drug (Lyfaquin®) for hypovolemic/hemorrhagic shock in India, and US FDA has approved the phase III IND application. It is anticipated that the phase III trial in the USA will begin in 2023. Thus, we have demonstrated that α2 ARs could be suitable targets for treating or managing hypovolemic/hemorrhagic shock. Further understanding of ARs in shock would help find new potential pharmacological targets.